Update on assessment and management of primary cardiac involvement in systemic sclerosis. Issue 1 (February 2018) - Bournia, Vasiliki-Kalliopi; Tountas, Christos; Protogerou, Athanase D.; Panopoulos, Stylianos; Mavrogeni, Sophie; Sfikakis, Petros P.
Primary cardiac involvement is a common and severe complication of systemic sclerosis, which may affect all of the hearts' structural components, including pericardium, myocardium, endocardium, cardiac valves, and conduction system. While cardiac disease can be clinically silent and only diagnosed in autopsy, new imaging modalities such as speckle-tracking echocardiography and cardiovascular magnetic resonance may reveal various abnormal findings in the majority of patients. Cardiovascular magnetic resonance evaluation should include assessment of left and right ventricular function, inflammation (STIR T2-weighted sequences (T2-W) for edema detection), and fibrosis (T1-weighted sequences 15 min after Gd-DTPA contrast medium injection (late-gadolinium enhancement). Notably, cardiac disease is responsible for about one-fourth of systemic sclerosis–related deaths. Systematic studies for the assessment and therapy of systemic sclerosis–related cardiac complications, as well as relevant guidelines from the European League Against Rheumatism and the American College of Rheumatology, are currently lacking. However, research advances reviewed herein allow for a better understanding of the mechanisms that alter cardiac function. Implementation of such knowledge should reduce cardiac morbidity and mortality in systemic sclerosis patients.